EVALUATION OF THE GOVERNANCE OF THE STAFFING SYSTEM ON THE PORCH OF THE RESEARCH AND STANDARDIZATION OF THE INDUSTRY BANDAR LAMPUNG USING THE COBIT FRAMEWORK - Ochi Marshella Febriani; Arie Setya Putra (IJISCS (International Journal of Information System and Computer Science), 2019)
This research was conducted to help research and standardization of Industrial halls Bandar lampung in evaluating system of tatakelola kepegawaiannya. Particular Audit presence in the system as a whole in the use, benefits, and results were found from the utilization of IT tatakelola. By evaluating it staffing company governance systems can automatically detect accurately what is written about the actions of lies and so forth in the staffing system tailored to the regulation of GR No. 53 of the year 2010. System audit is carried out will make it easier to find flaws in it, and the benefit system. the Cobit (control objectives for information and related technology) that calculates overall and evaluate tatakelola IT Audit. produce recommendations for improvements to the staffing system and will provide a solution for the company.